Correlation between Exercise and Sleep Quality of Bank Security Guard at Surakarta - Saputri, Rindy; Kiyatno, .; Suryawan, Arif (Nexus Kedokteran Komunitas, 2015)
Background: Security guard often experience sleep disturbances, especially insomnia due to the changing of sleep pattern. This sleep disturbance causes a decrease sleep quality on security guard. Exercise can prevent the decrease of sleep quality. This research aimed to determine the correlation between exercise and sleep quality of banks security guard in Surakarta. Methods: This was an observational analytic research with crosssectional design, which was held on November 2014 with security guard at Surakarta as the research subjects. Sampling method used simple random sampling. The dependent variable was sleep quality which was measured by questionnaire. The independent variable was exercise. The variable was measured by time accumulation of exercise in a week. It was categorized into exercise (â¥150 minutes/week) and non exercise (<150 minutes/week). Thirty eight research subjects was analyzed using Spearman correlation test. Result: The Spearman correlation test analysis showed a statistically significant strong correlation between exercise and sleep quality. Exercise had contribution 44.9% to improved sleep quality (R= 0.67; R2= 0.44; p=0.000). Conclusion: Exercise has strong positive correlation with sleep quality of bank security guard. Security officers who do exercise have better sleep quality. Key Words: Security guard, Sleep quality, Exercise.Â